Sarup phon b̄ưangton kānčhattham kh̨ōmūn sathiti ph̄ưa kānphatthanā ʻ̨Ōb̨ōt̨ō. Ph̨ō. S̨ō. 2547 phāitai khrōngkān čhattham rabop kh̨ōmūn sathiti radap th̨ōngthin r̄ưang khwāmd̄ưatr̨ōn kh̨ōng rātsad̨ōn læ khwāmt̨ōngkān hai ratthabān chūail̄ưa (Samnakngān Sathiti h̄æng Chāt, Krasūang Thēknōlōyī Sārasonthēt læ Kāns̄ưsān, 2004)
On 2004 statistical survey for the social development of the provinces of Thailand.